Media and Public Spheres
XII, 250 p.
Keywords: Using examples from the US, Europe and Asia,this collection presentsempirical studies of print, recorded music, movies, radio, television and the Internetto reveal both how media structure public spheresand how people use media to participate in the public sphere.